2020
DOI: 10.1136/bmjopen-2020-037416
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with knowledge and attitude towards adult cardiopulmonary resuscitation among healthcare professionals at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia: an institutional-based cross-sectional study

Abstract: ObjectiveThis study was conducted to assess the factors associated with knowledge and attitude towards adult cardiopulmonary resuscitation (CPR) among health professionals at the University of Gondar Hospital, Northwest Ethiopia.Study designAn institutional-based cross-sectional study was conducted from 15 February to 15 March 2018. Both bivariable and multivariable logistic regression analyses were used to identify factors associated with knowledge and attitude level of health professionals towards CPR. Varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 33 publications
1
22
1
Order By: Relevance
“…25 , 26 Furthermore, a study conducted in Gondar, Ethiopia, differed from this one in that 79.6% of study participants were aware of the signs of airway blockage. 27 The discrepancy could be related to the study’s utilization of a variety of health providers, as well as the study’s setting and study period. However, the current study’s findings are remarkably identical to those of Gangadevi Nandasena’s study, which found that 84.3% of the study subjects had knowledge of blocked airway care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 , 26 Furthermore, a study conducted in Gondar, Ethiopia, differed from this one in that 79.6% of study participants were aware of the signs of airway blockage. 27 The discrepancy could be related to the study’s utilization of a variety of health providers, as well as the study’s setting and study period. However, the current study’s findings are remarkably identical to those of Gangadevi Nandasena’s study, which found that 84.3% of the study subjects had knowledge of blocked airway care.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to those reported in studies by Gondar Comprehensive Hospital in Ethiopia and Ali M. Alabdali, who found that 71.7% and 69.4% of respondents, respectively, were aware of airway opening maneuvers. 27 , 30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in Saudi Arabia revealed that higher income and education levels were significantly associated with higher knowledge scores towards BLS. Another study in Saudi Arabia also showed that respondents' age, higher education, and attending training courses significantly increased knowledge of BLS information [4].…”
Section: Discussionmentioning
confidence: 95%
“…Research conducted in Addis Ababa also revealed that respondents who received first aid training were almost 5 times more likely to have adequate knowledge of BLS compared to respondents who did not attend training. Community knowledge about BLS is as important as the care provided in the hospital [4].…”
Section: Discussionmentioning
confidence: 99%